KEPASTIAN HUKUM ATAS TUMPANG TINDIH (OVERLAPPING) HAK KEPEMILIKAN ATAS TANAH DI TINJAU HUKUM POSITIF DI INDONESIA - Ni Gusti Ayu Devina Kumalasari; Komang Febrinayanti Dantes; Ni Luh Wayan Yasmiati (Berajah Journal, 2026)
There has been little research on the regulation and resolution of land ownership rights overlap, and the general people does not have a clear understanding of their legal status when it comes to Indonesia's land tenure system. The primary objective of this research is to ascertain whether or whether there is a clear legal framework addressing the issue of overlapping land ownership rights; the secondary objective is to examine, from a positive law standpoint, how such rights are regulated and resolved under Indonesian law. The primary objective of this research is to clarify some aspects of the Main Agrarian Law, Government Regulation 24 of 1997 on Land Registration, and any other relevant implementing regulations. Normative juridical study often makes use of conceptual analysis and legislative examination as its methodology. A thorough understanding of legal texts is achieved by qualitative research that employs primary, secondary, and tertiary sources. Inadequate public legal awareness, weak inter-agency coordination, mismatches between juridical and physical data, and a lack of certainty in the Indonesian land registration system all contribute to the reality of overlapping land ownership rights, according to the study. Legal procedures or mediation at the National Land Agency are examples of conventional methods for resolving disputes; nevertheless, the success of these methods relies heavily on the precision and thoroughness of the records maintained by the parties. As a result, we need to streamline the process of registering property, consolidate data from different sources, make the publicity principle more transparent, strengthen internal oversight, standardize regulations, and increase public access to legal education.